DOES ESG VALUE HAVE AN IMPACT ON A FIRM’S VALUE? LESSON LEARNED FROM INDONESIA - Lusiana Handayani; Clarashinta Canggih; Basyirah Ainun; Sahraman D. Hadjilatif (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
Introduction: With growing interests from investors and researchers in ethical investing—partly driven by the United Nations’ Sustainable Development Goals (SDGs)—this study examines the connection between Socially Responsible Investments (SRI) and Islamic finance. Given that these two approaches share common objectives, this study investigates the integration of Environmental, Social, and Governance (ESG) disclosure with Islamic screening principles that affect a firm’s value. Methods: The study focuses on companies listed on the Indonesia Sharia Stock Index (ISSI). It employes pooled Ordinary Least Squares (OLS) with a Random Effect Model (REM) to analyze the impact of ESG on firm value. Results: The findings indicate that ESG scores significantly affect a company’s operations, financial performance, and market standing. However, the impact varies depending on the specific ESG factors. Governance factors demonstrate a stronger association with firm value compared to environmental, economic, and social factors. Conclusion and suggestion: This results suggest that while ESG reporting is crucial, the specific focus areas highlighted in a company’s sustainability disclosures can influence performance in different ways. Strong evidence shows that sustainability reports significantly impact organizational performance. Furthermore, sharia-compliant companies are encouraged to emphasize Islamic values within their sustainability reporting to enhance transparency and appeal to investors. For Sharia-compliant companies in Indonesia, strategically integrating and transparently reporting ESG principles, especially those aligning with Islamic values, is becoming essential for enhancing financial performance, complying with new regulations, and attracting Muslim investors.